iPhone and iOS forensics investigation, analysis, and mobile security for Apple iPhone, iPad, and iOS devices - Hoog, Andrew; Strzempka, Katie (Syngress/Elsevier, 2011)
iPhone and iOS Forensics is a guide to the forensic acquisition and analysis of iPhone and iOS devices, and offers practical advice on how to secure iOS devices, data and apps. The book takes an in-depth look at methods and processes that analyze the iPhone/iPod in an official legal manner, so that all of the methods and procedures outlined in the text can be taken into any courtroom. It includes information data sets that are new and evolving, with official hardware knowledge from Apple itself to help aid investigators. This book consists of 7 chapters covering device features and functions; file system and data storage; iPhone and iPad data security; acquisitions; data and application analysis; and commercial tool testing. This book will appeal to forensic investigators (corporate and law enforcement) and incident response professionals.